Peranan Forum Koordinasi Pencegahan Terorisme (FKPT) dalam Melakukan Pencegahan Radikalisme (Analisis Perspektif Teori Struktural Fungsional) - Alfred, Alfred; Afrizal, Afrizal; Jendrius, Jendrius (Universitas Islam Negeri Imam Bonjol Padang, 2020)
Radicalism (Understanding) and terrorism (Action) are one unit which is a latent danger that is difficult to detect. This danger can be seen from the large number of victims falling from both government and civilian agencies. Someone who has been indoctrinated will find it difficult to get out of their wrong and anti-human understanding. However, people who have not yet been exposed to radical terror doctrines can still be straightened out through socialization, counseling and so on. This article aims to see how the West Sumatra Terrorism Prevention Coordination Forum - Forum Koordinasi Pencegahan Terorisme (FKPT) plays its role in preventing radicalism in West Sumatra. This paper uses a qualitative research approach, which the author then analyzes from the perspective of functional structural theory. The focus of FKPT activities is in the form of socialization. This outreach is aimed at people who are vulnerable to being exposed to the influence of radicalism. FKPT is different from the police or Densus 88 which specifically handles enforcement (legal) aspects, this FKPT specifically handles all matters related to prevention. So, researchers found that FKPT West Sumatra carried out its function in preventing radicalism in West Sumatra. This function and role can be seen from the activities carried out by FKPT West Sumatra in preventing radicalism. Radikalisme (Pemahaman) dan terorisme (Tindakan) adalah satu kesatuan yang merupakan bahaya laten yang sulit untuk dideteksi. Bahaya tersebut dapat dilihat dari banyaknya korban jatuh baik itu dari instansi pemerintah maupun sipil. Seseorang yang sudah ter-indoktrinisasi akan sulit keluar dari pemahamannya yang keliru dan anti kemanusiaan. Namun, masyarakat yang masih belum terpapar doktrin radikal teror masih bisa diluruskan dengan sosialisasi, penyuluhan dan lainnya. Tulisan ini bertujuan untuk melihat cara Forum Koordinasi Pencegahan Terorisme (FKPT) Sumatera Barat memainkan peranannya dalam melakukan pencegahan radikalisme di Sumatera Barat. Tulisan ini menggunakan pendekatan penelitian kualitatif yang selanjutnya penulis analisis dari perspektif teori struktural fungsional. Fokus dari kegiatan FKPT ini berbentuk sosialisasi. Sosialisasi ini ditujukan kepada masyarakat yang rentan terpapar pengaruh Radikalisme. FKPT berbeda dengan polisi atau Densus 88 yang khusus menangani aspek penindakan(hukum), FKPT ini khusus menangani segala hal terkait dengan pencegahan. Maka, peneliti mendapati FKPT Sumatera Barat menjalankan fungsinya dalam melakukan pencegahan radikalisme di Sumatera Barat. Fungsi dan peranan ini terlihat dari kegiatan yang dilakukan FKPT Sumatera Barat dalam melakukan pencegahan radikalisme.